Gerakan Literasi Mahasiswa: Studi Kasus Gerakan Literasi Komunitas Akar Sosial di Universitas Muhammadiyah Makassar - Wibowo, A. Arika; Azis, Fatimah; Kaharuddin, Kaharuddin; Maemunah, Maemunah (Indonesian Journal Publisher, 2023)
The problem in this study examines the literacy movement of sociology students who are members of a social root community that does not use campus intra-organizations (HMJ) as a forum for literacy movements. This study aims to find out why the literacy movement of sociology students who are members of a social root community uses the form of community as a forum for their literacy movement. This research is a qualitative descriptive research and uses an intrinsic case study approach. The results of this study indicate that the choice of community as a container movement is a strategy in the social root community literacy movement. The conclusion from this study is that apart from being a literacy movement strategy used by pioneering social root communities, it is also an alternative platform compared to using non-strategic intra-organizations as a movement platform.